2023
DOI: 10.1002/ptr.7786
|View full text |Cite
|
Sign up to set email alerts
|

Magnolia officinalis L. bark extract and respiratory diseases: From traditional Chinese medicine to western medicine via network target

Abstract: The understanding of the use of Magnolia officinalis L. (Magnoliaceae) as a possible dietary supplement for supporting the treatment of airway pathologies might be of clinical interest. Two commercially available bark extracts (M. officinalis extract [MOE]) were characterized by quantitation in honokiol and magnolol content by means of high-performance liquid chromatography with UV detection. MOE effects, as well as those of the reference compounds per se, on some targets connected to airway pathologies (antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…The antibacterial activity against S. aureus , P. aeruginosa , and Streptococcus pneumoniae , as well as the spasmolytic and antispasmodic effects, can be attributed to the ability of M. officinalis to simultaneously modulate several targets, including H 1 , β 2 , muscarinic receptors, and L‐type calcium involved in bronchodilation. These effects are largely associated with the concentration of specific secondary metabolites present in the extract, among which magnolol and honokiol stand out (Fontana et al, 2023).…”
Section: The Phytocomplexmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity against S. aureus , P. aeruginosa , and Streptococcus pneumoniae , as well as the spasmolytic and antispasmodic effects, can be attributed to the ability of M. officinalis to simultaneously modulate several targets, including H 1 , β 2 , muscarinic receptors, and L‐type calcium involved in bronchodilation. These effects are largely associated with the concentration of specific secondary metabolites present in the extract, among which magnolol and honokiol stand out (Fontana et al, 2023).…”
Section: The Phytocomplexmentioning
confidence: 99%
“…M. officinalis has a wide variety of traditional uses for the remedy of GI disorders such as dyspepsia, abdominal distension, and constipation. It possesses antispasmodic effects on isolated guinea pigs and mice's GI tract (Fontana et al, 2023), affecting the peristaltic activity; thus, it could be used as a nutraceutical for the management of GI disorders such as diarrhea associated with muscle spasms (Chan et al, 2008; Peng et al, 2010). Recent studies have shown that an ethanol extract of M. officinalis bark (1–10 mg/mL) depolarizes the cultured murine small intestine interstitial cells of Cajal, responsible for GI spontaneous motility.…”
Section: The Phytocomplexmentioning
confidence: 99%
“…Currently, Honokiol and Magnolol isolated from Magnolia officinalis are available on the active compounds market to treat several human diseases, respiratory diseases [ 22 , 130 ], cancer [ 131 , 132 ], obesity [ 133 ], intestinal problems, and gastric disturbances [ 22 ]. In this review, we suggest that the use of Magnolia active compounds against agriculture pests has a huge economic potential, for example: (I) Terpenoids: β-caryophyllene has an insecticide effect on Hymenoptera and Coleoptera [ 80 , 87 ], β-phellandrene and α-terpinene have an insecticide effect on Coleoptera [ 83 , 84 ], p -cymene has an insecticide effect on Diptera [ 85 ], and E-nerolidol has an insecticide effect on Hemiptera [ 93 ].…”
Section: Magnolia : Between Bioprospection and Conservationmentioning
confidence: 99%